Quantitative risk assessment for infectious disease introduction in animal populations: a comprehensive review - Marques, Ana Rita Pinheiro; Gonzalez Villeta, Laura; Simons, Robin; Horigan, Verity; de Vos, Clazien; Conrady, Beate (Frontiers in Veterinary Science, 2025)
IntroductionQuantitative risk assessments (QRA) are valuable decision-support tools for estimating disease introduction risks in animal populations.MethodsThis review analyzed peer-reviewed QRA studies published between 2010 and 2024 that focused on risk of introduction, aiming to identify methodological trends and challenges.ResultsFrom the 1,933 studies screened, only 34 (2%) met inclusion criteria, primarily assessing risk through movements of live animals (n = 20), animal products (n = 7), both live animals and their products (n = 2), or vectors (n = 5), with no studies addressing aquatic animals. Most QRAs focused on livestock (n= 11 ruminants, n = 6 swine, n = 4 poultry, n = 2 equids and n = 1 ruminants and swine) and diseases like Foot-and-mouth disease, Rabies, Lumpy skin disease, and African swine fever using stochastic approaches, frequently based on scenario tree and WOAH based methodology and supported by expert opinion. Cluster and network analyses revealed distinct methodological groupings and two main collaboration hubs in Europe and the United States.ConclusionKey gaps included limited coverage of certain animal species, pathogens, and consequence assessments, with a predominant focus on import risks. Addressing these limitations can strengthen future QRAs as input for animal disease management.